Tax Knowledge among University Professors: A case of Makawanpur Multiple Campus - Bidari, Dinesh; Sigdel, Niranjan; Shrestha, Suman; Paudel, Ram Sharan; Bidari, Sandesh (International Research Journal of MMC, 2023)
Tax knowledge plays vital role in tax compliance. The objective of this study is to assess overall and faculty wise level of tax knowledge among lecturers of Makawanpur Multiple Campus. Descriptive research design is applied by adopting survey method to collect data. Out of 83 total lecturers, 69 are selected for the study as respondent through stratified sampling method with proportionate sampling technique by making four clusters Management, Science, Humanities and Education. Questionnaire has been administered with five points likert scale ranging from not at all aware(1) to extremely aware(5).The results shows that overall tax knowledge of lecturers are less than average (i.e. slightly aware). However, lecturers of management faculty who have studied tax education have higher than average i.e. very aware. Result indicates that tax education is important for understanding taxpayer’s right responsibility, allowable deduction and other technical tax knowledge. It is concluded that Curriculum Development Center of Tribhuvan University and Inland Revenue Department should coordinate to develop curriculum and technical tax knowledge program among taxpayer for minimizing non-compliance problems by enhancing tax knowledge.